2020
DOI: 10.4081/dr.2020.8312
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in black African patients with keloid scars

Abstract: A keloid scar is a benign skin tumor and we aimed to assess the Quality of Life (QoL) of black Africans with keloid scars based on the Dermatology Life Quality Index (DLQI). We conducted a cross-sectional descriptive study in the department of dermatology of the teaching hospital of Treichville in Ivory Coast. We recruited 132 patients with keloid and 3612 dermatoses without keloid: The prevalence was 3.50% (132/3753). We included 120 patients aged from 16 to 63 years old, the sex ratio was 0.46 (38/82) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…We excluded pain and pruritus from the final multivariable analysis because they are subjective and may be a result of severe keloids rather than be risk factors for their development; however, pain and pruritus are common in keloid patients. [12,40] Previous studies have reported that, after treatment with silicone gel sheets or cryosurgery, pathological examination shows fewer mast cells infiltrating the keloids, which is consistent with relief of pain and pruritus. [41,42] The persistent inflammation induced by mast cells, macrophages, or lymphocytes that contributes to the progression of keloids is strongly associated with pain and pruritusthe more severe the inflammatory reaction, the more pronounced these symptoms.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We excluded pain and pruritus from the final multivariable analysis because they are subjective and may be a result of severe keloids rather than be risk factors for their development; however, pain and pruritus are common in keloid patients. [12,40] Previous studies have reported that, after treatment with silicone gel sheets or cryosurgery, pathological examination shows fewer mast cells infiltrating the keloids, which is consistent with relief of pain and pruritus. [41,42] The persistent inflammation induced by mast cells, macrophages, or lymphocytes that contributes to the progression of keloids is strongly associated with pain and pruritusthe more severe the inflammatory reaction, the more pronounced these symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast to smaller growths, severe keloids are often ugly and accompanied by recurrent infections and significant pain or pruritus, all of which can greatly affect patients’ quality of life. [ 11 , 12 ] Although patients with such keloids strongly desire medical intervention, few effective treatment options are available for them. The main available options are surgery and radiotherapy, which often achieve relatively unsatisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…The development of keloid results in cosmetic disfigurement, pruritus, pain, and hyperesthesia resulting in impairment of health-related quality of life. It is usually seen in individuals between 10 and 30 years but can affect beyond sixth decade [6,7]. Lesser frequency of scar formation in elderly is attributed to reduction in skin tension and sebaceous gland activity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previously, such case was reported in 10 years review by Valinotti et al and Kassi K et al recently reported pruritis in 95% of 120 keloid cases with commonest site being ears (29.17%). 19,20 Pilot survey by Huang et al found 80% patients of ichthyosis with ear pruritus. 21 In the literature, Pentyala et al first-time reported pruritus associated with temporomandibular joint dysfunction in the inner ear.…”
Section: Discussionmentioning
confidence: 99%